NODULAR REGENERATIVE HYPERPLASIA OF THE LIVER AND PORTAL THROMBOSIS - Onur, M. Ruhi; Poyraz, A. Kursad; Kocakoc, E. (Assoc Royal Soc Scientifiques Medicales Belges, 2012)
[Abstract Not Available]
Keywords: Nodular regenerative hyperplasia - MRI; liver